Analysis Of Sharia Financial Literacy Understanding Among Generation Z At Tsanawiyah Tawee Wittaya Islam School Pattani Thailand - Muhammad Fadhil Hamdani; Rahmayat Rahmayat; Qurani Parang Wilwadigta (International Conference on Islamic Economic (ICIE), 2026)
This study is motivated by the low level of Islamic financial literacy among Generation Z in the midst of rapid digital financial development, which potentially encourages consumptive behavior without adequate understanding of Sharia principles. This study aims to analyze the level of Islamic financial literacy and identify the factors influencing students’ financial behavior at Tsanawiyah Tawee Wittaya Islam School, Pattani, Thailand. The research employs a qualitative approach with a case study design, using observation, semi-structured interviews with students, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings reveal that students’ Islamic financial literacy is at a moderate level, characterized by a relatively good understanding of basic concepts such as the prohibition of riba and the importance of responsible financial management, but limited understanding of contract mechanisms (akad), gharar and maysir, as well as their practical implementation in modern financial transactions. Family environment, social media influence, and the integration of Islamic values in education are identified as key determinants shaping students’ financial behavior. This study contributes by highlighting the gap between normative understanding and practical application of Islamic financial literacy in the context of Islamic education within a Muslim minority setting. The implications emphasize the need for more contextual, practice-based, and value-oriented financial literacy education to develop financially literate and ethically responsible generations in accordance with Sharia principles.